A meta-analysis into the mediatory effects of family planning utilization on complications of pregnancy in women of reproductive age - Jahanfar, Shayesteh; Maurer, Olivia; Lapidow, Amy; Oberoi, Anjali Rajkumari; Steinfeldt, Meredith; Ali, Moazzam (PLOS ONE, 2024)
Background Despite conflicting findings in the current literature regarding the correlation between contraceptives and maternal health consequences, statistical analyses indicate that family planning may decrease the occurrence of such outcomes. Consequently, it is crucial to assess the capability of family planning to mitigate adverse maternal health outcomes. Objectives This review investigates the effects of modern contraceptive use on maternal health. Search methods This systematic review is registered on Prospero (CRD42022332783). We searched numerous databases with an upper date limit of February 2022 and no geographical boundaries. Selection criteria We included observational studies, including cross-sectional, cohort, case-control studies, and non-RCT with a comparison group. We excluded systematic reviews, scoping reviews, narrative reviews, and meta-analyses from the body of this review. Main results The review included nineteen studies, with five studies reporting a reduction in maternal mortality linked to increased access to family planning resources and contraceptive use. Another three studies examined the impact of contraception on the risk of preeclampsia and our analysis found that preeclampsia risk was lower by approximately 6% among contraceptive users (95% CI 0.82–1.13) compared to non-users. Two studies assessed the effect of hormonal contraceptives on postpartum glucose tolerance and found that low-androgen contraception was associated with a reduced risk of gestational diabetes (OR 0.84, 95% CI 0.58–1.22), while DMPA injection was possibly linked to a higher risk of falling glucose status postpartum (OR 1.42, 95% CI 0.85–2.36). Two studies evaluated high-risk pregnancies and births in contraceptive users versus non-users, with the risk ratio being 30% lower among contraceptive users of any form (95% CI 0.61, 0.80). None of these results were statistically significant except the latter. In terms of adverse maternal health outcomes, certain contraceptives were found to be associated with ectopic pregnancy and pregnancy-related venous thromboembolism through additional analysis.